THE ROLE OF PUSKESMAS IN THE IMPLEMENTATION OF PHBS AT SLB ALPA KUMARA WARDANA II - Adila Rahana; Rachmat Hargono (Universitas Airlangga, 2018)
Puskesmas as a health service facility, organized public health effort and individuals in the first level. As a first-rate health facility, puskesmas are responsible for health in their working area. School is one of the institutions that become the responsibility of puskesmas. Health efforts in schools are realized through the development of health promotion. The development of school health promotion is implemented through a health program, UKS. UKS targets are all schools which means not only public schools but also specials schools (SLB) are included. Children with special needs is one of the human resources whose quality must be improved. Such quality improvement can be done through basic behavioral cultivation, including health behavior. PHBS in school is an absolute necessity. This can be said because the various diseases that often attack school-age children associated with PHBS. SLB Alpa Kumara Wardana II is one of the target schools of Puskesmas Pucang Sewu so that the implementation of PHBS from the school is also the responsibility of Puskesmas Pucang Sewu. This study aims to analyze the role of puskesmas in the implementation of PHBS in schools at SLB based on Ottawa Charter. The method used in this research is qualitative with the determination of informants using purposive sampling technique. The results obtained from this research is the role of puskesmas in the implementation of PHBS in schools at SLB Alpa Kumara Wardana II is still less than optimal in the implementation of PHBS in schools. Implementation of PHBS in SLB is still need to improved application from the aspect of build healthy public policy, create supportive environtment, reorient health services, strengthen community action, and develop personal skills.